Innovation, structural inspection for new mixed complexes: DNA binding, biomedical applications and molecular docking approaches - Faizah S. Aljohani; Tarek El-Dabea; Rafat M. El-Khatib; Aly Abdou; Seraj Alzahrani; Ibrahim Omar Barnawi; Mahmoud Abd El Aleem Ali Ali El-Remaily; Ahmed M. Abu-Dief (Journal of Taibah University for Science)
2-Guanidinobenzimidazole (BIG) and Imidiazole (I) ligands were utilized to synthesize Cu(II), VO(II), Ag(I), and Pd(II) as mixed ligand complexes. All studied molecules were characterized through various spectral, analytical and computational studies to find out their chemical structure. TGA was applied to identify the occurrence of H2O molecules besides the mono-nuclear property of isolated complexes. These complexes were proved through DFT study to confirm the coordinating site that was proposed and displays the optimal three-dimensional structures of the studied compounds. The binding affinity of the tested complexes with CT-DNA has been tested through agarose gel, electronic spectroscopy and viscosity measurements. Furthermore, the studied molecules might bind to CT-DNA electrostatically through exterior contact, replacement, intercalation and groove surface binding with good affinity. In-vitro anti-bacterial, anti-fungi, cytotoxic and antioxidant activities are performed for all studied compounds. MOE-docking simulation results indicate promising inhibitory features of BIGIPd complexes, in agreement with in-vitro results.